Data base of Impact of theatrical activities on perceptual-motor skills in early childhood education - Rojas Castañeda, Manuela (2025)
Body expression has historically been established as a fundamental didactic strategy in physical education for developing body awareness. In early childhood education, it is essential for acquiring motor skills and abilities that enable children to function effectively in diverse contexts. Theater, as a performing art of multidimensional nature, presents significant potential for the development of Perceptual-Motor Abilities (PMA). This research evaluated the impact of a theatrical intervention on the development of PMA in students aged 5 to 8 years at Reggio Emilia school. A quantitative study with a pre-experimental single-group design with pretest-posttest measurements was implemented. The sample consisted of 22 students. An evaluation battery specifically designed and validated for the Colombian context was used to assess PMA. The intervention consisted of a structured didactic unit of eight 60-minute sessions, implemented over four weeks with a frequency of two sessions per week. Theatrical activities included body expression exercises, improvisation, dramatization of stories, role-playing games, and group stage productions, progressively designed to stimulate different dimensions of PMA. Statistical analysis was performed using parametric tests to compare the means between pretest and posttest. The results showed statistically significant improvements (p<0.05) in all variables related to the assessed PMA. It is concluded that theater constitutes an effective pedagogical tool for promoting the development of perceptual-motor abilities in children, suggesting its systematic incorporation into early childhood physical education programs.